Enterohemorrhagic Escherichia coli responds to gut microbiota metabolites by altering metabolism and activating stress responses. (31st December 2023) - Vogt, Stefanie L.; Serapio-Palacios, Antonio; Woodward, Sarah E.; Santos, Andrew S.; de Vries, Stefan P.W.; Daigneault, Michelle C.; Brandmeier, Lisa V.; Grant, Andrew J.; Maskell, Duncan J.; Allen-Vercoe, Emma; Finlay, B. Brett
ABSTRACT: Enterohemorrhagic Escherichia coli (EHEC) is a major cause of severe bloody diarrhea, with potentially lethal complications, such as hemolytic uremic syndrome. In humans, EHEC colonizes the colon, which is also home to a diverse community of trillions of microbes known as the gut microbiota. Although these microbes and the metabolites that they produce represent an important component of EHEC's ecological niche, little is known about how EHEC senses and responds to the presence of gut microbiota metabolites. In this study, we used a combined RNA-Seq and Tn-Seq approach to characterize EHEC's response to metabolites from an in vitro culture of 33 human gut microbiota isolates (MET-1), previously demonstrated to effectively resolve recurrent Clostridioides difficile infection in human patients. Collectively, the results revealed that EHEC adjusts to growth in the presence of microbiota metabolites in two major ways: by altering its metabolism and by activating stress responses. Metabolic adaptations to the presence of microbiota metabolites included increased expression of systems for maintaining redox balance and decreased expression of biotin biosynthesis genes, reflecting the high levels of biotin released by the microbiota into the culture medium. In addition, numerous genes related to envelope and oxidative stress responses (including cpxP, spy, soxS, yhcN, and bhsA ) were upregulated during EHEC growth in a medium containing microbiota metabolites. Together, these results provide insight into the molecular mechanisms by which pathogens adapt to the presence of competing microbes in the host environment, which ultimately may enable the development of therapies to enhance colonization resistance and prevent infection.